Anchoring and ordering NGS contig assemblies by population sequencing (POPSEQ). (10th October 2013) - Mascher, Martin; Muehlbauer, Gary J.; Rokhsar, Daniel S.; Chapman, Jarrod; Schmutz, Jeremy; Barry, Kerrie; Muñoz‐Amatriaín, María; Close, Timothy J.; Wise, Roger P.; Schulman, Alan H.; Himmelbach, Axel; Mayer, Klaus F.X.; et al.
Summary: Next‐generation whole‐genome shotgun assemblies of complex genomes are highly useful, but fail to link nearby sequence contigs with each other or provide a linear order of contigs along individual chromosomes. Here, we introduce a strategy based on sequencing progeny of a segregating population that allows de novo production of a genetically anchored linear assembly of the gene space of an organism. We demonstrate the power of the approach by reconstructing the chromosomal organization of the gene space of barley, a large, complex and highly repetitive 5.1 Gb genome. We evaluate the robustness of the new assembly by comparison to a recently released physical and genetic framework of the barley genome, and to various genetically ordered sequence‐based genotypic datasets. The method is independent of the need for any prior sequence resources, and will enable rapid and cost‐efficient establishment of powerful genomic information for many species.